Regulating squeeze-out techniques by controlling shareholders: the divergence between Hong Kong and Singapore. Issue 1 (2nd January 2018) - Chen, Christopher; Zhang, Wei; Wan, Wai Yee
ABSTRACT: Squeeze-out transactions are controversial as the controlling shareholders may expropriate the minorities' shareholdings at unattractive prices. Existing scholarship has focused on the optimal approach towards regulating such transactions in the United States (US) and the United Kingdom (UK), which have widely dispersed public shareholdings, but little attention has been placed on jurisdictions with concentrated shareholdings, which may necessitate a different approach given that the prospects of expropriation are very high. This article fills the gap by examining Hong Kong and Singapore, which have concentrated shareholdings. Notwithstanding the fact that they have adapted their corporate and securities laws from the UK, Hong Kong ultimately provides greater minority shareholder protection than Singapore. We present empirical evidence that the differences in regulation have led to a smaller number of squeeze-outs but higher premiums payable to minority shareholders in Hong Kong, as compared to Singapore. However, Hong Kong firms experience higher levels of related party transactions prior to the squeeze-outs, which represent another form of tunnelling. We explain the differences in regulation and discuss the normative implications of our findings. Our study contributes to the broader literature that 'law matters' and provides case studies of how interest group politics shape the evolution of laws and regulation.